Are RNA-Based Tests Sufficient for COVID-19 Diagnosis? An Inspiration of Three Asymptomatic Cases. (3rd February 2021) - Hu, Tao; Liu, Xiao; Yin, Qinan; Duan, Xingting; Yan, Li
In this work, we discovered a new phenomenon—asymptomatic COVID-19 infection, or covert case, during the pandemic. All the 3 patients had a history of exposure, with no symptoms, and no abnormalities were found in computed tomography scan or lab tests. Except for case 2, the other patients' severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) nucleic acid tests were negative. But their anti-SARS-COV-2 nucleocapsid antibody showed a dynamic trend, consistent with the process of virus infection and clearance. A growing number of asymptomatic or covert cases need more attention. Lack of surveillance may lead to another outbreak. We hope to demonstrate our cases to attract the attention of governments or health authorities that covert cases should be the focus as well.